Penerapan Empati Layanan Masyarakat Melalui Pembagian Sembako Di Desa Babakan Karet Cianjur - Ari Ramdani; Elis Nurhayati; Raden Minda Kusumah; Rd. Ratih Hanawidjaya; Desta Sulaesih Mursyidah (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
This community service focuses on the application of community service empathy through the distribution of groceries in Babakan Karet Cianjur Village. This activity was carried out directly by distributing groceries to five hamlet heads in Babakan Karet Cianjur Village. The purpose of this community service activity is to apply service empathy to the community as a form of concern for fellow human beings. The implementation of this dedication received a positive response. However, it is hoped that community service activities of this type can be carried out in a sustainable and systematic manner